DETERMINATION OF YIELD AND QUALITY PARAMETERS OF SOME SAFFLOWER (CARTHAMUS TINCTORIUS L.) VARIETIES GROWN IN VAN ECOLOGICAL CONDITIONS - Lutfi Nohutcu; Ezelhan Selem; Ruveyde Tuncturk; Murat Tuncturk (Agricultura)
This study was conducted during 2019-2020 growing season at the experimental station of the Faculty of Agriculture, Van Yuzuncu Yil University in Türkiye, in order to determine the yield and yield components of some safflower varieties grown in irrigated conditions. The registered varieties including Ayaz, Asol, Olas, Yenice, Remzibey-05, Balci, Gokturk, Linas were studied in Completely Randomized Block designe with three replicates. Several parameters such as plant height, first branch height, number of main and secondary branches per plant, table number, seed number per head, thousand seed weight, hectolitre weight, seed yield, crude oil ratio as well as crude oil yield were measured. Results showed that  Asol and Olas varieties had the highest amounts of yield (1169.3 and 1046.3 kg ha-1), oil ratio (31.9% and 31.8%) and crude oil yield (374.7 and 333.4 kg ha-1), respectively. Based on results as well as  climatic and environmental conditions of the studied region, it is suggested to study more on the effects of different types and amounts of fertilizers on these two important plant varieties especially in in dry conditions  in order to recommend  for the region.